Impact of Recipient Age in Combined Liver-Kidney Transplantation: Caution Is Needed for Patients ≥70 Years - Burcin Ekser, MD, PhD; William C. Goggins, MD; Jonathan A. Fridell, MD; Plamen Mihaylov, MD; Richard S. Mangus, MD; Andrew J. Lutz, MD; Daiki Soma, MD, PhD; Marwan S. Ghabril, MD; Marco A. Lacerda, MD; John A. Powelson, MD; Chandrashekhar A. Kubal, MD, PhD (Transplantation Direct, 2020)
Background. Elderly recipients (≥70 y) account for 2.6% of all liver transplants (LTs) in the United States and have similar outcomes as younger recipients. Although the rate of elderly recipients in combined liver-kidney transplant (CLKT) is similar, limited data are available on how elderly recipients perform after CLKT. Methods. We have previously shown excellent outcomes in CLKT using delayed kidney transplant (Indiana) Approach (mean kidney cold ischemia time = 53 ± 14 h). Between 2007 and 2018, 98 CLKTs were performed using the Indiana Approach at Indiana University (IU) and the data were retrospectively analyzed. Recipients were subgrouped based on their age: 18–45 (n = 16), 46–59 (n = 34), 60–69 (n = 40), and ≥70 years (n = 8). Results. Overall, more elderly patients received LT at IU (5.2%) when compared nationally (2.6%). The rate of elderly recipients in CLKT at IU was 8.2% (versus 2% Scientific Registry of Transplant Recipient). Recipient and donor characteristics were comparable between all age groups except recipient age and duration of dialysis. Patient survival at 1 and 3 years was similar among younger age groups, whereas patient survival was significantly lower in elderly recipients at 1 (60%) and 3 years (40%) (P = 0.0077). Control analyses (replicating Scientific Registry of Transplant Recipient’s survival stratification: 18–45, 46–64, ≥65 y) showed similar patient survival in all age groups. Conclusions. Although LT can be safely performed in elderly recipients, extreme caution is needed in CLKT due to the magnitude of operation.